2022
DOI: 10.3389/fpsyg.2021.823499
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Measurement and Heterogeneity Analysis of Chinese Cultural and Creative Industries: Based on Three-Stage Data Envelopment Analysis Modified by Stochastic Frontier Analysis

Abstract: Industry sustainability plays a vital role in shaping the environment for cultural and creative business development. However, considering the influence of the external environment and random factors on the technical efficiency (T.E.) of cultural and creative industries with the inherent defects of the traditional data envelopment analysis (DEA) model; this manuscript analyzed the operating efficiency of 56 cultural and creative enterprises using the three-stage DEA model from 2012 to 2018. An analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Zeng et al (2016) apply a three‐stage DEA model to investigate the efficiency of investments made in the China's cultural industry in 2011, and suggest using government power to support the development of cultural industries in the western region. Li et al (2022) analyze the operational efficiency of 56 cultural and creative enterprises from 2012 to 2018. The results show that the overall efficiency of cultural and creative industries listed in China is relatively low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zeng et al (2016) apply a three‐stage DEA model to investigate the efficiency of investments made in the China's cultural industry in 2011, and suggest using government power to support the development of cultural industries in the western region. Li et al (2022) analyze the operational efficiency of 56 cultural and creative enterprises from 2012 to 2018. The results show that the overall efficiency of cultural and creative industries listed in China is relatively low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have conducted empirical studies on the input-output efficiency of the cultural industries that showed great variation among different provinces. The overall efficiency of the cultural and creative industries is recognized low in China, environmental factors had significant effects on the development of the cultural industries in each region ( Nusrat et al, 2021 ; Li et al, 2022 ). There are significant differences in the efficiency of cultural industries inputs and outputs in eastern, central, and western China.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The development of enterprises is closely related to organizational flexibility. The management mode that serves the organizational flexibility of enterprises and the increase of elastic demand is conducive to promoting the improvement of corporate revenue and profit (Li et al, 2022). Organizational flexibility can play a promoting role in the influence mechanism of a global innovation knowledge network on firm innovation capability (Korman et al, 1981).…”
Section: Moderating Role Of Organizational Flexibilitymentioning
confidence: 99%
“…In conclusion, based on the literature combing in the above section, the studies that have been conducted focus on venture capital, firm innovation performance (Rodríguez-Gulías et al, 2020), synergy models, heterogeneous knowledge sources and absorptive capacity (Santoro et al, 2020), government subsidies and digital technologies (Pierre et al, 2022), and efficiency analysis (Li et al, 2022) of cultural and creative firms, and so on, with insufficient attention to digital creative enterprises and fewer studies on knowledge sharing among employees of digital creative enterprises. Furthermore, there is a lack of quantitative research on the influencing factors such as psychological ownership of personal knowledge, social alienation, and organizational flexibility of employees in digital creative enterprises.…”
Section: Introductionmentioning
confidence: 99%